2015
DOI: 10.5660/wts.2015.4.3.225
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of Echinochloa colona (L.) Link from other Echinochloa Species using DNA Barcode

Abstract: Echinochloa colona is one of the most problematic weeds in the paddy fields of the world. In recent years, this species is likely to be introduced in Korea due to global warming, the expansion of international trade including agricultural products, and increasing tourists. We tried to identify the species from Korean Echinochloa crus-galli and E. oryzicola in order to establish the control measures in case of the initial influx. For this study, Echinochloa colona collected from the National Plant Germplasm Sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
(6 reference statements)
0
2
0
1
Order By: Relevance
“…Các mẫu lá đinh lăng sau khi ly trích DNA được sử dụng để thực hiện phản ứng PCR theo phương pháp Williams et al (1990). Trộn Master mix bao gồm: nước cất 2 lần, PCR buffer, dNTPs, MgCl 2 , mồi ITS1 và ITS4, Taq polymerase (Lee et al, 2015). Trình tự nucleotide của ITS1 và ITS4 (White et al, 1990) như sau: ITS1: 5'-TCCGTAGGTGAACCTGCGG-3' ITS4: 5'-TCCTCCGCTTATTGATATGC-3' Các mẫu DNA của cây đinh lăng sau khi thực hiện phản ứng PCR với mồi ITS sẽ được giải trình tự theo phương pháp của Sanger.…”
Section: Phương Pháp Ly Trích Mẫuunclassified
“…Các mẫu lá đinh lăng sau khi ly trích DNA được sử dụng để thực hiện phản ứng PCR theo phương pháp Williams et al (1990). Trộn Master mix bao gồm: nước cất 2 lần, PCR buffer, dNTPs, MgCl 2 , mồi ITS1 và ITS4, Taq polymerase (Lee et al, 2015). Trình tự nucleotide của ITS1 và ITS4 (White et al, 1990) như sau: ITS1: 5'-TCCGTAGGTGAACCTGCGG-3' ITS4: 5'-TCCTCCGCTTATTGATATGC-3' Các mẫu DNA của cây đinh lăng sau khi thực hiện phản ứng PCR với mồi ITS sẽ được giải trình tự theo phương pháp của Sanger.…”
Section: Phương Pháp Ly Trích Mẫuunclassified
“…The chloroplast genome of Echinochloa is highly conserved for its genome structure, organization, and gene order (Ye et al, 2014). So far, chloroplast genomes of seven Echinochloa species including E. crus-galli, E. ugandensis, E. stagnina, E. colona, E. esculenta, E. frumentacea, and E. oryzicola (Ye et al, 2014;Perumal et al, 2016;Lee et al, 2017;Sebastin et al, 2019) have been sequenced. It revealed their genome structure (quadripartite), identity (99.5%), and size (139,592-139,851 bp) of the chloroplast genomes.…”
Section: Chloroplast Genomes and Phylogeny Analysismentioning
confidence: 99%
“…Further, molecular divergence clock analysis of grass species revealed that Echinochloa species had diverged 21.6 Mya than others. The wild species, such as E. oryzicola and E. crus-galli, diverged around 3.3 Mya while another wild species, E. colona, diverged from E. oryzicola and E. crus-galli between 2.65 and 3.18 Mya, respectively (Lee et al, 2017). Later, the cultivated species (E. frumentacea) diverged from E. oryzicola and E. crus-galli in and around 1.9-2.7 Mya (Perumal et al, 2016) (Figure 5).…”
Section: Chloroplast Genomes and Phylogeny Analysismentioning
confidence: 99%